Association between peripheral nerve function and structure in human diabetic nerves. Issue 5 (8th May 2017) - Borire, Adeniyi; Issar, Tushar; Kwai, Natalie; Krishnan, Arun
Abstract : Objectives: We explored the nerve ultrasound (US) characteristics of diabetic patients and correlated these findings with clinical severity and electrophysiological parameters. Methods: One-hundred and twenty diabetic patients (90 type 2; 30 type 1) underwent comprehensive neurologic assessment, nerve conduction studies, US and excitability assessment. Neuropathy severity was assessed using Total Neuropathy Score (TNS). Median nerve sonographic assessment was performed at a non-entrapment site, to obtain the cross-sectional area (CSA) and vessel score. Power Doppler sonograms from nerves with detectable intraneural blood flow (INBF) were processed with PixelFlux to obtain the maximum perfusion intensity (MPI). Corresponding median motor excitability studies were performed. Results: Median nerve CSA was significantly higher in diabetic patients compared with controls (8.03±0.21 mm 2 vs 7.1±0.4 mm 2, p<0.05). 58% of the diabetes cohort had neuropathy (TNS>1), with larger nerves compared with non-neuropathic subjects (8.64±0.33 mm 2 vs 7.33±0.20 mm 2, p<0.05). Nerve size increased with worsening neuropathy severity, demonstrated by the correlation between CSA and TNS (r=0.496; p<0.0001). 20.3% of diabetic patients had detectable INBF compared with none in the control group (p<0.0001). Patients with detectable INBF had larger nerves (9.56±0.64 mm 2 vs 7.64±0.18 mm 2, p<0.05), and more severe neuropathy (p<0.05). A strong relationship was found between CSA and INBF (vessel score: r=0.475, p<0.01; MPI: r=403, p<0.01). Subgroup analysis revealed that CSA correlated significantly with excitability parameters in type 1 patients (TEd10-20 ms: r=−0.752, p<0.01; TEd40-60ms: r=−0.845, p<0.001; TEd90–100ms: r=−0.891, p<0.001; refractoriness: r=0.664, p<0.01). In contrast, no correlation was found between CSA and excitability parameters in type 2 patients. Conclusions: This study demonstrates significant nerve enlargement in diabetic patients, which correlates well with neuropathy severity, and may potentially be a biomarker for early diagnosis. Detectable INBF was predominantly seen in patients with moderate to severe neuropathy, suggesting that this may be a marker of severity or axonal loss. The study also provides further evidence that different pathophysiological mechanisms lead to the development of neuropathy in type 1 and type 2 diabetes.